Circulation, writing, and rhetoric - Gries, Laurie E., editor; Brooke, Collin Gifford, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2018)
It has been understood that writers quote, imitate, forward, borrow, dispute, engage with, and transform texts written by others. Contributors identify circulation as a threshold concept of Western literacy theory and explore five key themes concerning circulation: public rhetoric, feminism, new materialism, theories of delivery, and technologies.--Provided by publisher.
Making space in Lansing, Michigan: communities and/in circulation / Donnie Sackey, Jim Ridolfo, Danielle Nicole DeVoss -- Engaging circulation in urban revitalization / Michele Simmons -- Tombstones, QR codes, and the circulation of past present texts / Kathleen Blake Yancey -- Augmented publics / Casey Boyle, Nathaniel Rivers -- Ubicomposition: circulation as production and abduction in Carlo Ratti's smart environments / Sean Morey, John Tinnell -- Entanglements that matter: a new materialist trace of #Yesallwomen / Dustin Edwards, Heather Lang -- Re-evaluating girls' empowerment: towards a transnational feminist literacy / Rebecca Dingo -- "Reverse black-boxing" the emergence of the religious right: closing structural holes in the 1970s social networks / Naomi Clark -- Social circulation and legacies of mobility for nineteenth century women: implications for using digital resources in socio-rhetorical projects / Jacqueline Jones Royster, Gesa E. Kirsch -- New rhetorics of scholarship: leveraging betweenness and circulation for feminist historical work in composition studies / Tarez Samra Graban, Patricia Sullivan -- For public distribution / Dale M. Smith, Jim Brown -- Cryptocurrency and persuasive network logics: from the circulation of rhetoric to the rhetoric of circulation / Gerald Jackson -- Circulation analytics: software development and social network data / Aaron Beveridge -- Open access(ibility?) / Jay Dolmage -- Circulation exhaustion / Jenny Rice -- Archival problems, circulation solutions / Jessica Enoch -- Circulation-signification-ontology / Thomas Rickert -- Circulation response: a diagrammatics of persuasion / Byron Hawk -- The spaces between / Sid Dobrin -- Afterword: the futurity of circulation studies / Laurie E. Gries.
Keywords: Rhetoric -- Social aspects; Communication in learning and scholarship